AN EMPIRICAL STUDY ON PENSION FUNDS’ PORTFOLIO AND INVESTMENT PERFORMANCE: THE EFFECT OF PENSION FUNDS’ SIZE - Yulia Vidya Nanda; Apriani Dorkas Rambu Atahau (Jurnal Manajemen dan Kewirausahaan, 2020)
This study seeks to investigate whether larger pension funds exhibit better investment performance than smaller ones and differences in the selection of investment instruments between large and small pension funds. Our research sample is 13 pension funds that are the members of BKS Dapen-KI (Badan Kerja Sama Dana Pensiun Kristen Indonesia – the Cooperation Council of Christian Pension Fund in Indonesia) in 2010-2017. We use the quantitatively descriptive and independent-sample t-test methods. The results indicate no significant difference between the performance of large and small pension funds likely because both pension fund types have relatively similar total assets. However, large and small pension funds have exhibit different investment instruments selection.